The application of robotic transanal minimally invasive surgery in rectal surgery - Guodong Xiao; Bin Huang; Zhengyong Liu; Chunxue Li; Weidong Tong (Intelligent Surgery)
With its superior ergonomic design, high-definition three-dimensional visual field, mechanical arms that transcend human wrist mobility, and ability to eliminate hand tremors caused by surgeon fatigue, the robotic surgical system introduces unparalleled precision and adaptability into intricate surgical procedures within confined areas, particularly the anorectal region. This makes it a strong competitor to laparoscopic-assisted, minimally invasive transanal surgery. The application of robotic surgery has been successfully demonstrated in the resection of complex rectal tumors, total rectal mesentery resection, and fistula repair. These procedures have resulted in notable improvements in surgical precision, safety, and patients' postoperative quality of life. Despite the continued presence of challenges, including prolonged operation time and high cost, the long-term benefits and positive impact on patients' quality of life have become increasingly evident. This article presents a comprehensive overview of the development of robotic-assisted minimally invasive transanal surgery, its evolving application, and the remaining controversies surrounding its use.